Endophthalmitis and blebitis following deep sclerectomy and trabeculectomy with routine use of mitomycin C. Issue 3 (9th November 2022) - Kankainen, Tuulia; Harju, Mika
Abstract: Purpose: The purpose of the study was to investigate the incidence for endophthalmitis and blebitis after deep sclerectomy (DS) and trabeculectomy with routine use of Mitomycin C (MMC) 0.4 mg/ml. Methods: Electronic medical records of patients who underwent surgery 1/2008–4/2020 were reviewed. Cumulative incidence for bleb‐associated infection (BAI), including both endophthalmitis and blebitis, was calculated with cumulative incidence function (CIF) and Kaplan–Meier analysis. Risk factors for BAI were evaluated with univariate competing risk regression analysis and Log‐rank analysis. Competing event in CIF was death. Results: In this retrospective single‐centre cohort study, a total of 2653 patients and 3411 eyes underwent surgery: 3478 glaucoma surgeries, 2419 DS and 1059 trabeculectomies. Two cases of endophthalmitis and three of isolated blebitis developed. Median follow‐up from the most recent surgery on the eye until the end of the study was 5.5 years, and until last visit at the ophthalmology department was 1.9 years. For the whole follow‐up period in CIF‐analysis, cumulative incidence for BAI was 0.16% (95% CI 0.06–0.36) at five years. Incidence was higher with eyes not treated with an antifibrotic during surgery (sub‐hazard ratio 11.66, 95% CI 1.94–70.21, p = 0.007). Cumulative incidence between surgery and last visit with Kaplan–Meier analysis was 0.21% (95% CI 0.08–0.52) at five years, similarly, not using an antifibrotic increased incidence (Log‐rank p < 0.001). Conclusion: Cumulative incidence for BAI was low despite routine use of high‐dose MMC.